PERBANDINGAN EKSTRAK LAMUR Aquilaria malaccensis DENGAN METODE MASERASI DAN REFLUKS - Syamsul, Eka Siswanto; Amanda, Nadhila Ajrina; Lestari, Dwi (Jurnal Riset Kefarmasian Indonesia, 2020)
Gaharu (Aquilaria malaccensis Lamk) is a plant of the thymelaeaceae family that is widely used by the people of West Kutai Regency as a medicinal plant for skin wounds, diabetes, asthma, stomach pain and sleep disorders, aromatherapy and used as ingredients for perfume because it has a distinctive aroma. The extraction process will determine how much yield is produced. This study aims to determine the percent (%) yield of agarwood leaf ethanol extract using maceration and reflux methods. The research stage includes plant determination, sample processing, extraction using maceration and reflux methods with 70% ethanol solvent, determination of the yield and phytochemical screening. Data analysis in the form of descriptive data analysis and presented in tabular form. The results showed that the reflux method produced a higher average yield of 30.70% and maceration method of 29.97%. Statistical test results using the Independent Sample T-Test method showed that there was no significant difference in the yield produced from the maceration and reflux method because (p> 0.05). Phytochemical screening test results showed that agarwood leaf extract contains flavonoids, tannins, saponins and steroids